Announcement of Retraction - Lee, Jean (Business Management and Strategy, 2021)
The editorial board announced this article has been retracted on April 14, 2022. If you have any further question, please contact us at: bms@macrothink.org Article Title: The Impact of “Product Planning and Design” and “Sales Ability” on Financial Performance by Taiwan-Listed Construction Companies: An Intervening Variable of Macro Environmental Factors Author/s: Kuo-Wei Tsai, Huei-Jeng Chou, Hsing-Chau Tseng Journal Title: Business Management and Strategy ISSN 2157-6068 Volume and Number: Vol. 12, No. 1, 2021 Pages: 29-47 DOI: 10.5296/bms.v12i1.18104